Glass fiber impregnating compound composition, glass fiber impregnating compound, glass fiber product and application

By using glass fiber wetting agent compositions of silane coupling agents, film forming agents, antioxidants and accelerators, the problem of thermal oxygen aging of PBT glass fiber composites is solved, and its mechanical properties and thermal oxygen aging resistance are significantly improved.

CN119707320AActive Publication Date: 2025-03-28JUSHI GRP CO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411883799.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Existing PBT glass fiber composite materials are susceptible to thermal oxygen aging, resulting in degradation of performance.

Method used

A glass fiber wetting agent composition, including a silane coupling agent, a film forming agent, an antioxidant and accelerator, is used to improve the compatibility of the glass fiber with PBT resin and the thermal oxygen aging resistance.

Benefits of technology

It significantly enhances the mechanical properties of the composite material after PBT resin, and significantly improves its thermal oxygen aging resistance, extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198801820000071
    Figure BDA0005198801820000071
  • Figure BDA0005198801820000081
    Figure BDA0005198801820000081
  • Figure BDA0005198801820000082
    Figure BDA0005198801820000082
Patent Text Reader

Abstract

The invention provides a glass fiber impregnating compound composition, a glass fiber impregnating compound, a glass fiber product and application. The glass fiber impregnating compound composition comprises effective components and water, and the effective components comprise the following components in percentage by mass: 5.0%-15.0% of a silane coupling agent, 55.0%-80.0% of a film-forming agent, 4.0%-12.0% of an antioxidant and 8.0%-30.0% of an accelerant; wherein the solid content of the impregnating compound composition is 6.0%-15.0%. According to the glass fiber impregnating compound composition disclosed by the invention, through synergistic cooperation of the components, glass fiber chopped strands produced by adopting the glass fiber impregnating compound composition are good in bundling property, small in hairiness amount in production and use processes and good in compatibility with polybutylene terephthalate, so that the mechanical property of a polybutylene terephthalate composite material is remarkably enhanced, and the service life of the polybutylene terephthalate composite material is prolonged. And the thermo-oxidative aging resistance is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a glass fiber sizing composition and a glass fiber sizing, a glass fiber product and an application thereof. Background Art

[0002] Polybutylene terephthalate (PBT) has the characteristics of excellent mechanical properties, electrical properties and good dimensional stability. After being reinforced with glass fiber, the mechanical properties, thermal properties and dimensional stability are further improved, and the good electrical properties are still retained after reinforcement. Therefore, it is widely used in the fields of electronics, home appliances, automobiles, machinery, etc. Although the existing PBT glass fiber composite materials have good mechanical properties and heat resistance, they will be attacked by heat and oxygen during long-term use, resulting in performance deterioration, such as yellowing and whitening, and their performance will gradually decrease. Thermal oxidative aging is one of the important factors affecting the performance of PBT glass fiber composite materials, which will lead to the deterioration of the mechanical properties, thermal properties and appearance quality of the material.

[0003] Therefore, developing a sizing that can effectively resist thermal oxidative aging is crucial to extend the service life of PBT glass fiber composites. Summary of the invention

[0004] The main purpose of the present invention is to provide a glass fiber sizing composition and a glass fiber sizing, a glass fiber product and application, so as to solve the problem of easy thermal oxidation aging of PBT glass fiber composite materials in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a glass fiber sizing composition, comprising effective components and water, wherein the effective components comprise, by mass percentage, 5.0% to 15.0% of a silane coupling agent, 55.0% to 80.0% of a film-forming agent, 4.0% to 12.0% of an antioxidant and 8.0% to 30.0% of an accelerator; wherein the solid content of the sizing composition is 6.0% to 15.0%; the silane coupling agent is an epoxy silane coupling agent, the film-forming agent is an epoxy emulsion and / or a polyurethane emulsion, the antioxidant is a hindered phenol antioxidant, and the accelerator is an aromatic amine accelerator.

[0006] Furthermore, in terms of mass percentage, the above-mentioned effective components include: 6.0% to 13.0% of a silane coupling agent, 60.0% to 70.0% of a film former, 5.0% to 10.0% of an antioxidant and 12.0% to 19.0% of an accelerator; wherein the solid content of the wetting agent composition is 7.0% to 14.0%; preferably, the effective components include: 7.5% to 12.0% of a silane coupling agent, 65.0% to 70.0% of a film former, 6.0% to 10.0% of an antioxidant and 14.0% to 19.0% of an accelerator.

[0007] Furthermore, the ratio of the dry weight of the epoxy emulsion to the dry weight of the polyurethane emulsion is 1:1 to 6:1, preferably 1:1 to 3:1.

[0008] Furthermore, the epoxy silane coupling agent is selected from any one or more of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyl ether propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and γ-glycidyl ether propyltriethoxysilane type silane coupling agents.

[0009] Furthermore, the epoxy emulsion is a phenolic modified epoxy emulsion and / or a bismaleimide modified epoxy emulsion, and the polyurethane emulsion is an aliphatic polyurethane emulsion and / or a polyolefin type polyurethane emulsion.

[0010] Furthermore, the hindered phenol antioxidant is selected from any one or more of alkyl monophenol compounds, alkyl polyphenol compounds and thiopolyphenol compounds.

[0011] Furthermore, the aromatic amine accelerator is selected from any one or more of diaminodiphenylmethane, diaminodiphenyl sulfone and 3,3'-diethyl-4,4'-diaminodiphenylmethane.

[0012] According to another aspect of the present invention, a glass fiber sizing is provided, which is obtained by mixing a glass fiber sizing composition, and the glass fiber sizing composition is the above-mentioned glass fiber sizing composition.

[0013] According to yet another aspect of the present invention, a glass fiber product produced by coating the glass fiber sizing agent is provided.

[0014] According to another aspect of the present invention, there is provided a use of the above-mentioned glass fiber product in reinforcing a polybutylene terephthalate resin composite material.

[0015] Applying the technical scheme of the present invention, the film-forming agent of the sizing agent of the present application is a combination of epoxy emulsion and / or polyurethane emulsion. Epoxy resin has good compatibility with polybutylene terephthalate (PBT resin), so that the final product has excellent mechanical properties and gives the composite material more excellent heat-resistant oxygen aging performance. The selected epoxy emulsion improves the combination of glass fiber and PBT resin, and gives the composite material better stability of heat-resistant oxygen aging. At the same time, the selected polyurethane emulsion has excellent film-forming properties, and the glass fiber coated with polyurethane has better processability, which helps to improve the heat-resistant oxygen aging performance of the composite material. At the same time, the film-forming agent used in the present application needs to be controlled within a certain range. If the amount of the film-forming agent is too much, it will cause the glass fiber to be too strong in clustering and difficult to disperse, reducing the mechanical properties of the composite material; if the amount of the film-forming agent is too little, it will cause the glass fiber surface wear resistance to deteriorate, and the increase of hairiness will affect the smoothness of production and easily cause the appearance of floating fibers. Therefore, it is preferred to control the amount of the film-forming agent within the above range. The antioxidant used in this application is a hindered phenol antioxidant, which is different from ordinary antioxidants due to the uniqueness of its structure. Hindered phenol antioxidants are a class of compounds with substituted groups on one or both sides of the -OH on the benzene ring. In most cases, its structure includes two tert-butyl groups. Since the hydroxyl group is restricted by spatial barriers, the hydrogen atom (H) can easily fall off from the original molecular structure, thereby achieving the effect of donating protons and combining with peroxyl radicals (ROO-), alkyl radicals, hydroxyl radicals, etc., causing it to lose its original activity, resulting in the termination of the oxygen aging reaction. The amount of antioxidant is an important factor affecting the heat-resistant oxygen aging performance of glass fiber in PBT resin. If the amount of antioxidant is too much, the product bundling will be poor, resulting in more hairiness of glass fiber during extrusion, and the performance will be reduced; if the amount of antioxidant is too little, it will not have the effect of improving the heat-resistant oxygen aging performance. Therefore, this application controls the amount of antioxidant within the above range. The accelerator is an aromatic amine accelerator, which contains an oil-stable benzene ring structure in its molecular structure. Due to the presence of the benzene ring, the accelerator itself has high heat resistance. At the same time, the amine can also promote the curing and cross-linking reaction of epoxy resin. At the same time, the amount of accelerator must also be controlled within a certain range. As the amount of curing agent increases, the tensile and bending properties of the composite material will first increase and then decrease. Therefore, the application controls the amount of accelerator within the above range. The silane coupling agent in the present application is an epoxy silane coupling agent, which can cooperate with the above types of film-forming agents, antioxidants and accelerators to effectively improve the compatibility of glass fiber and PBT resin. At the same time, the amount of silane coupling agent needs to be controlled within a suitable range. If the amount of silane coupling agent is too much, the color of the product will be yellowish, and the dispersion of glass fiber in the resin will also deteriorate, which will affect the final heat-resistant oxygen aging performance; if the amount of silane coupling agent is too little, the mechanical properties of the composite material will not meet the design requirements. Therefore, it is preferred to control the amount of silane coupling agent within the above range.Through the synergistic coordination of the above components, the glass fiber chopped strands produced by the above glass fiber sizing composition have good bundling properties, less hairiness during production and use, good compatibility with PBT resin, significantly enhanced mechanical properties of the PBT resin composite material, and significantly improved heat and oxygen aging resistance. DETAILED DESCRIPTION

[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0017] As analyzed in the background technology of this application, there is a problem in the prior art that PBT glass fiber composite materials are prone to thermal oxidative aging. In order to solve the above problem, this application provides a glass fiber sizing composition and a glass fiber sizing, a glass fiber product and application.

[0018] In a typical embodiment of the present application, a glass fiber sizing composition is provided, comprising effective components and water, wherein the effective components comprise, by mass percentage, 5.0% to 15.0% of a silane coupling agent, 55.0% to 80.0% of a film former, 4.0% to 12.0% of an antioxidant and 8.0% to 30.0% of an accelerator; wherein the solid content of the sizing composition is 6.0% to 15.0%; the silane coupling agent is an epoxy silane coupling agent, the film former is an epoxy emulsion and / or a polyurethane emulsion, the antioxidant is a hindered phenol antioxidant, and the accelerator is an aromatic amine accelerator.

[0019] The film-forming agent of the sizing agent of the present application is a combination of epoxy emulsion and / or polyurethane emulsion. Epoxy resin has good compatibility with polybutylene terephthalate (PBT resin), so that the final product has excellent mechanical properties and gives the composite material more excellent heat-resistant oxygen aging performance. The selected epoxy emulsion improves the combination of glass fiber and PBT resin, and gives the composite material better stability of heat-resistant oxygen aging. At the same time, the selected polyurethane emulsion has excellent film-forming properties, and the glass fiber coated with polyurethane has better processability, which helps to improve the heat-resistant oxygen aging performance of the composite material. At the same time, the film-forming agent used in the present application needs to be controlled within a certain range. If the amount of the film-forming agent is too much, it will cause the glass fiber to be too strong in clustering and difficult to disperse, reducing the mechanical properties of the composite material; if the amount of the film-forming agent is too little, it will cause the glass fiber surface wear resistance to deteriorate, and the increase of hairiness will affect the smoothness of production and easily cause the appearance of floating fibers. Therefore, it is preferred to control the amount of the film-forming agent within the above range. The antioxidant used in this application is a hindered phenol antioxidant, which is different from ordinary antioxidants due to the uniqueness of its structure. Hindered phenol antioxidants are a class of compounds with substituted groups on one or both sides of the -OH on the benzene ring. In most cases, its structure includes two tert-butyl groups. Since the hydroxyl group is restricted by spatial barriers, the hydrogen atom (H) can easily fall off from the original molecular structure, thereby achieving the effect of donating protons and combining with peroxyl radicals (ROO-), alkyl radicals, hydroxyl radicals, etc., causing it to lose its original activity, resulting in the termination of the oxygen aging reaction. The amount of antioxidant is an important factor affecting the heat-resistant oxygen aging performance of glass fiber in PBT resin. If the amount of antioxidant is too much, the product bundling will be poor, resulting in more hairiness of glass fiber during extrusion, and the performance will be reduced; if the amount of antioxidant is too little, it will not have the effect of improving the heat-resistant oxygen aging performance. Therefore, this application controls the amount of antioxidant within the above range. The accelerator is an aromatic amine accelerator, which contains an oil-stable benzene ring structure in its molecular structure. Due to the presence of the benzene ring, the accelerator itself has high heat resistance. At the same time, the amine can also promote the curing and cross-linking reaction of epoxy resin. At the same time, the amount of accelerator must also be controlled within a certain range. As the amount of curing agent increases, the tensile and bending properties of the composite material will first increase and then decrease. Therefore, the application controls the amount of accelerator within the above range. The silane coupling agent in the present application is an epoxy silane coupling agent, which can cooperate with the above types of film-forming agents, antioxidants and accelerators to effectively improve the compatibility of glass fiber and PBT resin. At the same time, the amount of silane coupling agent needs to be controlled within a suitable range. If the amount of silane coupling agent is too much, the color of the product will be yellowish, and the dispersion of glass fiber in the resin will also deteriorate, which will affect the final heat-resistant oxygen aging performance; if the amount of silane coupling agent is too little, the mechanical properties of the composite material will not meet the design requirements. Therefore, it is preferred to control the amount of silane coupling agent within the above range.Through the synergistic coordination of the above components, the glass fiber chopped strands produced by the above glass fiber sizing composition have good bundling properties, less hairiness during production and use, good compatibility with PBT resin, significantly enhanced mechanical properties of the PBT resin composite material, and significantly improved heat and oxygen aging resistance.

[0020] In addition, the solid mass of each effective component in the present application refers to the mass of the non-water component of the corresponding effective component. The water in the present application is the dispersed phase of each effective component in the glass fiber sizing composition, wherein the water is preferably deionized water.

[0021] In order to further improve the synergistic effect of the effective components in the glass fiber sizing composition and make each component perform better, in one embodiment of the present application, the effective components preferably include, by mass percentage, 6.0% to 13.0% of a silane coupling agent, 60.0% to 70.0% of a film-forming agent, 5.0% to 10.0% of an antioxidant and 12.0% to 19.0% of an accelerator; wherein the solid content of the sizing composition is 7.0% to 14.0%; further preferably, the effective components include: 7.5% to 12.0% of a silane coupling agent, 65.0% to 70.0% of a film-forming agent, 6.0% to 10.0% of an antioxidant and 14.0% to 19.0% of an accelerator.

[0022] In one embodiment of the present application, the ratio of the dry weight mass of the epoxy emulsion to the dry weight mass of the polyurethane emulsion is 1:1 to 6:1, preferably 1:1 to 3:1.

[0023] Film formers are one of the most important ingredients in glass fiber sizing compositions, and determine the performance of glass fiber production, processing, and PBT resin composites reinforced therewith. The use of a mixture of epoxy emulsion and polyurethane emulsion is beneficial to the mechanical properties and performance of glass fiber. The higher the proportion of epoxy emulsion, the better the binding property with PBT resin; on the contrary, polyurethane emulsion is mainly used for better bundling, less hairiness, and better performance. Therefore, it is preferred to control the ratio of the dry weight mass of the above-mentioned epoxy emulsion to the dry weight mass of the polyurethane emulsion within the above-mentioned range, which is more conducive to compatibility of the performance of epoxy emulsion and polyurethane emulsion, thereby making the comprehensive performance of glass fiber better. It depends on the specific needs. For example, the ratio of the dry weight mass of epoxy emulsion to the dry weight mass of polyurethane emulsion is 1:1, 2:1, 3:1, 4:1, 5:1 or 6:1.

[0024] In one embodiment of the present application, the epoxy silane coupling agent is selected from any one or more of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyl ether propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and γ-glycidyl ether propyltriethoxysilane type silane coupling agents.

[0025] The silane coupling agent in the present application can make the glass fiber and the PBT resin have a coupling effect, which can repair the micro cracks of the glass fiber during the production process, and also affect the compatibility and interface bonding between the glass fiber and the PBT resin, thereby affecting the mechanical properties of the composite material. Specifically, the preferred epoxy silane coupling agent of the above type has excellent high temperature resistance, better compatibility with the PBT resin, and a relatively milder reaction speed, which is more helpful to improve the interface bonding between the glass fiber and the PBT resin.

[0026] In addition, this application uses epoxy silane coupling agents and no longer uses other coupling agents. From the experimental results, a single epoxy coupling agent has the best thermal oxygen aging resistance effect on the composite material. The addition of amino or other types of silane coupling agents will reduce the final thermal oxygen aging resistance. It is speculated that the possible reason is that after the addition of amino silanes, the bonding between the glass fiber filaments becomes stronger, which affects the dispersion performance of the glass fiber to a certain extent, and the uniformity of the resin becomes relatively worse. Other types of silane coupling agents, such as A174, have poor compatibility with PBT resin, and adding them to it will affect the combination of glass fiber and resin.

[0027] In one embodiment of the present application, the epoxy emulsion is a phenolic modified epoxy emulsion and / or a bismaleimide modified epoxy emulsion, and the polyurethane emulsion is an aliphatic polyurethane emulsion and / or a polyolefin type polyurethane emulsion.

[0028] Film-forming agent can protect glass fiber from wear and tear during wire drawing, maintain the clustering of yarn, can improve the compatibility of glass fiber and PBT resin when reinforcing resin, and the film-forming agent after special modification can also give the final composite material more functional characteristics. Therefore, select suitable film-forming agent, can ensure the clustering of yarn and the smoothness in post-order use, can ensure that glass fiber and matrix resin are mixed evenly and interface bonding effect is sufficient and complete, thereby improve the mechanical properties of composite material and product, and give composite material more excellent heat-resistant oxygen aging performance. The present application preferably phenolic modified epoxy emulsion and / or bismaleimide modified epoxy emulsion, phenolic epoxy resin (EPN) chemical name linear phenolic polyglycidyl ether, light brown viscous liquid, is a kind of heat-resistant epoxy resin. Bismaleimide (BMI for short) is another type of resin system derived from the polyimide resin system. It is a bifunctional compound with maleimide (MI) as the active end group. It has similar fluidity and moldability to epoxy resin and can be processed and molded by methods similar to epoxy resin. The preferred epoxy emulsion above helps to improve the heat resistance of epoxy resin, thereby improving the heat and oxygen aging resistance of glass fiber.

[0029] In one embodiment of the present application, the hindered phenol antioxidant is selected from any one or more of alkyl monophenol compounds, alkyl polyphenol compounds and thiopolyphenol compounds.

[0030] The selection of a suitable antioxidant can provide glass fiber with better temperature resistance, improve the anti-aging performance of the sizing agent, improve the color of the composite product, and improve the anti-aging performance of the composite material. The above types of antioxidants used in this application help to terminate the aging reaction more timely and accurately.

[0031] In one embodiment of the present application, the aromatic amine accelerator is selected from any one or more of diaminodiphenylmethane, diaminodiphenyl sulfone and 3,3'-diethyl-4,4'-diaminodiphenylmethane.

[0032] The use of the accelerator in the present application increases the reaction degree of the epoxy resin in the sizing agent, increases the crosslinking degree after the reaction, and improves the interface bonding between the glass fiber and the PBT resin. The aromatic amine accelerator of the above type is preferably higher in heat resistance and is conducive to further promoting the curing crosslinking reaction of the epoxy resin.

[0033] In another typical embodiment of the present application, a glass fiber sizing is provided, which is obtained by mixing a glass fiber sizing composition, and the glass fiber sizing composition is the above-mentioned glass fiber sizing composition.

[0034] The glass fiber sizing agent in the present application is obtained by mixing the above-mentioned glass fiber sizing agent composition. The glass fiber sizing agent can significantly enhance the mechanical properties of the composite material after PBT resin, and the heat-oxidative aging resistance is significantly improved.

[0035] In some optional embodiments, a method for preparing the aforementioned glass fiber sizing is provided, comprising the following steps:

[0036] S1: hydrolysis of silane coupling agent: adding the silane coupling agent into water, hydrolyzing the silane coupling agent, and stirring until the solution is clear to obtain a silane coupling agent solution;

[0037] S2: dilution of film former, antioxidant and accelerator: dilute the film former, antioxidant and accelerator with water respectively;

[0038] S3: Add the diluted film-forming agent, antioxidant and accelerator to the silane coupling agent solution, make up the remaining amount of water, and stir evenly to obtain the glass fiber sizing agent.

[0039] In some optional embodiments, step S1 includes: adding water in an amount of 20 to 40 times the weight of the silane coupling agent into a first container, adding the silane coupling agent into the first container, hydrolyzing the silane coupling agent, stirring while adding, stirring until the solution is clear and there are no oil droplets on the surface, to obtain a silane coupling agent solution.

[0040] In some optional embodiments, step S2 includes: adding water at room temperature whose weight is 1 to 2 times of the weight of the film-forming agent into the second container, and then slowly adding the film-forming agent, stirring and dissolving, to obtain the film-forming agent diluted with water;

[0041] Adding water at room temperature in an amount 1 to 2 times the weight of the antioxidant into the third container, then slowly adding the antioxidant, stirring and dissolving, to obtain an antioxidant diluted with water;

[0042] Add room temperature water whose weight is 1 to 2 times of the weight of the accelerator into the fourth container, then slowly add the accelerator, stir and dissolve, and obtain the accelerator diluted with water.

[0043] It should be noted that the terms "1S" and "2S" in this article are only used to more clearly explain the technical solution of the present application, and are not intended to limit the present application; in the preparation process, the order of step 1S and step 2S can be adjusted according to actual conditions. Moreover, the use of water to dilute the film-forming agent, antioxidant and accelerator can also be adjusted according to actual needs, which will not be elaborated here.

[0044] In another typical embodiment of the present application, a glass fiber product produced by coating the above-mentioned glass fiber sizing agent is provided.

[0045] The glass fiber product produced by coating the above-mentioned glass fiber sizing agent has both excellent mechanical properties and heat-oxidative aging resistance.

[0046] In some optional embodiments, the chopped length of the glass fiber product is 2 to 9 mm, preferably 2.5 to 7.5 mm, and more preferably 3 to 6 mm.

[0047] In another typical embodiment of the present application, there is provided a use of the above-mentioned glass fiber product in reinforcing a polybutylene terephthalate resin composite material.

[0048] The glass fiber product has great improvement effect and economic value, especially in the application of reinforcing polybutylene terephthalate resin composite materials.

[0049] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0050] In order to more clearly explain the technical solution of the present application, some specific embodiments (Examples 1 to 18) of the glass fiber sizing composition of the present application are listed below, wherein the specific formulas of the glass fiber sizing composition of Examples 1 to 18 of the present application are shown in Table 1, and the amount of each effective component in Table 1 is the percentage of the solid mass of the corresponding effective component to the total solid mass of the sizing agent.

[0051] It should be pointed out that the specific types, contents and combinations of the components selected in Table 1 do not limit the protection scope of the present application.

[0052] Table 1 Sizing agent composition formula of Examples 1 to 18

[0053]

[0054]

[0055] Table 1 (Continued) Sizing agent composition formulations of Examples 1 to 18

[0056]

[0057]

[0058] Table 1 (Continued) Sizing agent composition formulations of Examples 1 to 18

[0059]

[0060]

[0061] The preparation method of the glass fiber sizing of embodiments 1 to 18 specifically comprises the following steps:

[0062] Hydrolysis of silane coupling agent: adding silane coupling agent into water, hydrolyzing the silane coupling agent, stirring until the solution is clear, and obtaining a silane coupling agent solution;

[0063] Dilution of film former, antioxidant and accelerator: dilute the film former, antioxidant and accelerator with water respectively;

[0064] The diluted film-forming agent, antioxidant and accelerator are added into the silane coupling agent solution, the balance of water is added, and the mixture is stirred evenly to obtain the glass fiber sizing agent.

[0065] In addition, in order to further illustrate the beneficial effects of the present application, the following impregnating agent formulations (Comparative Examples 1 to 3) are selected as comparative examples, wherein Comparative Example 3 is a currently commonly used impregnating agent for glass fiber reinforced with polybutylene terephthalate resin, which is convenient for comparison with the technical solution of the present application.

[0066] Comparative Example 1

[0067] The wetting agent contains effective components and water, with a solid content of 9.0%. The percentage of the solid mass of each effective component to the total solid mass of the wetting agent is expressed as follows:

[0068] Coupling agent (amino silane coupling agent): 15%;

[0069] Film former (bisphenol A epoxy resin and polyether polyurethane): 75%;

[0070] Lubricant (silicone oil lubricant): 10%.

[0071] Comparative Example 2

[0072] The wetting agent contains effective components and water, with a solid content of 8.5%. The percentage of the solid mass of each effective component to the total solid mass of the wetting agent is expressed as follows:

[0073] Coupling agent (amino silane coupling agent and epoxy silane coupling agent): 10%;

[0074] Film former (alicyclic epoxy emulsion): 80%;

[0075] Lubricant (polyether lubricant): 10%.

[0076] Comparative Example 3

[0077] The wetting agent contains effective components and water, with a solid content of 8.0%. The percentage of the solid mass of each effective component to the total solid mass of the wetting agent is expressed as follows:

[0078] Coupling agent (amino silane coupling agent): 10%;

[0079] Film former (mixture of bisphenol A epoxy and polyurethane-urea emulsion): 76%;

[0080] Antioxidant (phosphite antioxidant): 14%.

[0081] The preparation method of the glass fiber sizing agent of Comparative Examples 1 to 3 specifically comprises the following steps:

[0082] Hydrolysis of the coupling agent: adding the coupling agent into water, hydrolyzing the coupling agent, and stirring until the solution is clear to obtain a coupling agent solution;

[0083] Dilution of film former, antioxidant and accelerator: dilute the film former, antioxidant and accelerator with water respectively;

[0084] The diluted film-forming agent, antioxidant and accelerator are added to the coupling agent solution, the remaining amount of water is supplemented, and the mixture is stirred evenly to obtain the glass fiber sizing agent.

[0085] Performance testing:

[0086] The present application conducted comparative tests on the performance of Examples 1 to 18 and Comparative Examples 1 to 3, and the test method is as follows:

[0087] The sizing agents of Examples 1 to 18 and Comparative Examples 1 to 3 were respectively applied to produce glass fibers, and the corresponding glass fibers were baked and chopped to produce chopped strands, with a chopped length of 3 mm.

[0088] Then the corresponding chopped glass fibers were melt-mixed and extruded into granules with polybutylene terephthalate resin to finally obtain glass fiber reinforced polybutylene terephthalate resin composite materials (glass fiber content of 30%), and part of the composite materials were placed in a constant temperature oven at 205°C and taken out after 48 hours to retest the performance. The performance test results are shown in Table 2.

[0089] Tensile Strength: ISO 527-1-2012.

[0090] Flexural Strength: ISO 178-2010.

[0091] Unnotched impact strength: ISO 179-1-2010.

[0092] Notched impact strength: ISO 179-1-2010.

[0093] Table 2 Performance test results of the embodiments and comparative examples

[0094]

[0095]

[0096] Table 2 (Continued) Performance test results of embodiments and comparative examples

[0097]

[0098] Table 2 (Continued) Performance test results of embodiments and comparative examples

[0099]

[0100] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0101] The film-forming agent of the sizing agent of the present application is a combination of epoxy emulsion and / or polyurethane emulsion. Epoxy resin has good compatibility with polybutylene terephthalate (PBT resin), so that the final product has excellent mechanical properties and gives the composite material more excellent heat-resistant oxygen aging performance. The selected epoxy emulsion improves the combination of glass fiber and PBT resin, and gives the composite material better stability of heat-resistant oxygen aging. At the same time, the selected polyurethane emulsion has excellent film-forming properties, and the glass fiber coated with polyurethane has better processability, which helps to improve the heat-resistant oxygen aging performance of the composite material. At the same time, the film-forming agent used in the present application needs to be controlled within a certain range. If the amount of the film-forming agent is too much, it will cause the glass fiber to be too strong in clustering and difficult to disperse, reducing the mechanical properties of the composite material; if the amount of the film-forming agent is too little, it will cause the glass fiber surface wear resistance to deteriorate, and the increase of hairiness will affect the smoothness of production and easily cause the appearance of floating fibers. Therefore, it is preferred to control the amount of the film-forming agent within the above range. The antioxidant used in this application is a hindered phenol antioxidant, which is different from ordinary antioxidants due to the uniqueness of its structure. Hindered phenol antioxidants are a class of compounds with substituted groups on one or both sides of the -OH on the benzene ring. In most cases, its structure includes two tert-butyl groups. Since the hydroxyl group is restricted by spatial barriers, the hydrogen atom (H) can easily fall off from the original molecular structure, thereby achieving the effect of donating protons and combining with peroxyl radicals (ROO-), alkyl radicals, hydroxyl radicals, etc., causing it to lose its original activity, resulting in the termination of the oxygen aging reaction. The amount of antioxidant is an important factor affecting the heat-resistant oxygen aging performance of glass fiber in PBT resin. If the amount of antioxidant is too much, the product bundling will be poor, resulting in more hairiness of glass fiber during extrusion, and the performance will be reduced; if the amount of antioxidant is too little, it will not have the effect of improving the heat-resistant oxygen aging performance. Therefore, this application controls the amount of antioxidant within the above range. The accelerator is an aromatic amine accelerator, which contains an oil-stable benzene ring structure in its molecular structure. Due to the presence of the benzene ring, the accelerator itself has high heat resistance. At the same time, the amine can also promote the curing and cross-linking reaction of epoxy resin. At the same time, the amount of accelerator must also be controlled within a certain range. As the amount of curing agent increases, the tensile and bending properties of the composite material will first increase and then decrease. Therefore, the application controls the amount of accelerator within the above range. The silane coupling agent in the present application is an epoxy silane coupling agent, which can cooperate with the above types of film-forming agents, antioxidants and accelerators to effectively improve the compatibility of glass fiber and PBT resin. At the same time, the amount of silane coupling agent needs to be controlled within a suitable range. If the amount of silane coupling agent is too much, the color of the product will be yellowish, and the dispersion of glass fiber in the resin will also deteriorate, which will affect the final heat-resistant oxygen aging performance; if the amount of silane coupling agent is too little, the mechanical properties of the composite material will not meet the design requirements. Therefore, it is preferred to control the amount of silane coupling agent within the above range.Through the synergistic coordination of the above components, the glass fiber chopped strands produced by the above glass fiber sizing composition have good bundling properties, less hairiness during production and use, good compatibility with PBT resin, significantly enhanced mechanical properties of the PBT resin composite material, and significantly improved heat and oxygen aging resistance.

[0102] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A glass fiber sizing composition comprising an effective component and water, characterized in that: In terms of mass percentage, the effective components include: 5.0% to 15.0% silane coupling agent; 55.0% to 80.0% film former; 4.0% to 12.0% antioxidant; 8.0% to 30.0% accelerator; The solid content of the sizing agent composition is 6.0% to 15.0%; the silane coupling agent is an epoxy silane coupling agent, the film-forming agent is an epoxy emulsion and / or a polyurethane emulsion, the antioxidant is a hindered phenol antioxidant, and the accelerator is an aromatic amine accelerator.

2. The glass fiber sizing composition according to claim 1, characterized in that: In terms of mass percentage, the effective components include: 6.0% to 13.0% of the silane coupling agent; 60.0% to 70.0% of the film-forming agent; 5.0% to 10.0% of the antioxidant; 12.0% to 19.0% of the accelerator; Wherein, the solid content of the sizing agent composition is 7.0% to 14.0%; Preferably, the effective components include: 7.5% to 12.0% of the silane coupling agent; 65.0% to 70.0% of the film-forming agent; 6.0% to 10.0% of the antioxidant; 14.0% to 19.0% of the accelerator.

3. The glass fiber sizing composition according to claim 1 or 2, characterized in that: The ratio of the dry weight mass of the epoxy emulsion to the dry weight mass of the polyurethane emulsion is 1:1 to 6:1, preferably 1:1 to 3:

1.

4. The glass fiber sizing composition according to any one of claims 1 to 3, characterized in that: The epoxy silane coupling agent is selected from any one or more of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyl ether propyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane and γ-glycidyl ether propyltriethoxysilane type silane coupling agents.

5. The glass fiber sizing composition according to any one of claims 1 to 4, characterized in that: The epoxy emulsion is a phenolic modified epoxy emulsion and / or a bismaleimide modified epoxy emulsion, and the polyurethane emulsion is an aliphatic polyurethane emulsion and / or a polyolefin type polyurethane emulsion.

6. The glass fiber sizing composition according to any one of claims 1 to 5, characterized in that: The hindered phenol antioxidant is selected from any one or more of alkyl monophenol compounds, alkyl polyphenol compounds and thiopolyphenol compounds.

7. The glass fiber sizing composition according to any one of claims 1 to 6, characterized in that: The aromatic amine accelerator is selected from any one or more of diaminodiphenylmethane, diaminodiphenyl sulfone and 3,3'-diethyl-4,4'-diaminodiphenylmethane.

8. A glass fiber sizing agent obtained by mixing a glass fiber sizing agent composition, characterized in that: The glass fiber sizing composition is the glass fiber sizing composition according to any one of claims 1 to 7.

9. A glass fiber product produced by coating the glass fiber sizing according to any one of claims 1 to 8.

10. Use of the glass fiber product according to claim 9 in reinforcing polybutylene terephthalate resin composite materials.

Citation Information

Patent Citations

  • Alkali-free direct roving impregnating compound for continuous fiber reinforced polyolefin

    CN104045244A

  • Glass fiber impregnating compound and application thereof

    CN113896436A

  • Impregnating compound for chopped glass fiber and preparation method, product and application thereof

    CN115818985A

  • Multilayer coating

    CN1505596A

  • Elastomeric coating composition for glass fibers and coated glass fibers made from same

    US4268577A